Different space characteristics of air temperature variation in North Sumatra Indonesia. (April 2020) - Prasetya, T A E; Munawar,; Chesoh, S; Lim, A; McNeil, D R
Abstract: Land Surface Temperature (LST) can be used as an indicator of measuring temperature change in the regions. The changing variation can be produced or affected by some factors such as elevation, land cover products, and Normalized Difference Vegetation Index (NDVI). This study aimed to investigate LST variation based on elevation, land cover products, and NDVI in the North Sumatra area, Indonesia. Land products satellite data between 2000 and 2018 were downloaded from the moderate resolution imaging spectroradiometer (MODIS) website. Multiple linear regression was used to find the patterns of LST variation. The highest LST variation was found in Evergreen Broadleaf (EB) forest and urban area with the average change 0.4 and 0.5 °C/decade and the lowest was found in water surface area with the average change more than -1 °C/decade. The overall mean of LST changing was -0.1 °C/decade with r-square 31.4%. There was a unique LST variation in EB forest land cover when the elevation increased, the LST also increased from -0.4 to 0.5 °C/decade. The same condition also appears in Savannas and cropland/natural vegetation mosaic (Crop. Mos.). In conclusion, the changing of LST in North Sumatra was affected by elevation, land cover products, and NDVI.